Analisis faktor-faktor yang mempengaruhi penerimaan dan penggunaan aplikasi mobile banking pada bank buku 4 di Indonesia dengan menggunakan model unified theory of acceptance and use of technology 2 - Setiadi, Hidayat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of increasingly advanced technology supports the birth of various new product and service innovations in the banking industry so that an information technology (IT)-based business strategy is very important to gain competitive advantage and business competition. Increasing the need for ease of transactions anywhere and anytime as well as changes in banking transactions made by the public from cash transactions to non-cash (digital) transactions have resulted in significant growth in mobile banking transactions in Indonesia. Although the number of transactions using mobile banking in Indonesia continues to increase, the process of digitizing banking services is considered a bit late compared to technology-based financial services or fintech. The level of consumer acceptance as a user becomes an essential problem because it is one of the determining factors for the success of an implemented system. This study was conducted to determine what factors in the UTAUT 2 model affect the use of BUKU 4 Bank mobile banking in Indonesia. The research was conducted quantitatively, PLS-SEM data analysis with SmartPLS 3, and online questionnaire distribution in Greater Jakarta (Jakarta, Bogor, Depok, Tangerang, South Tangerang, and Bekasi). The result is that the four hypotheses proposed were declared insignificant and rejected (Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation), the other four hypotheses were declared significant and accepted (Price Value, Facilitating Condition, Habit, Behavioral Intention).